2013
DOI: 10.5209/rev_clac.2012.v52.41089
|View full text |Cite
|
Sign up to set email alerts
|

Titles in Veterinary Medicine research articles

Abstract: Titles are the first point of contact between authors and readers. They call for attention and provide concise and exhaustive information on the research. State of the art in the medical field shows that titles have a mean word count ranging from 15.48 to 15.85 and that they can be arranged into four different formats: nominal, full-sentence, compound and question. Veterinary Medicine has not been object of study and is an underrepresented field in genre analytical surveys. This research wants to fill in part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 25 publications
2
15
1
Order By: Relevance
“…A present-tense sentence, which is the clearest way to express a conclusion about a result, accounted for 67.9% of results-mention titles in our corpus. Our observations are also consistent with Soler's [19] finding of more full sentences (declaratives, usually in the present tense) in biology RA titles (51%) than medical ones (16%). Biology RAs would be more similar to reports of in vitro or animal models in medicine, and when we checked their prevalence in our corpus a posteriori, we found that the NEJM and BMJ had none whereas the two anesthesiology journals had 17 (almost 13% of their total) and that 8 of them were full sentences.…”
Section: Phrasing Patterns In Ra and Review Titlessupporting
confidence: 82%
See 4 more Smart Citations
“…A present-tense sentence, which is the clearest way to express a conclusion about a result, accounted for 67.9% of results-mention titles in our corpus. Our observations are also consistent with Soler's [19] finding of more full sentences (declaratives, usually in the present tense) in biology RA titles (51%) than medical ones (16%). Biology RAs would be more similar to reports of in vitro or animal models in medicine, and when we checked their prevalence in our corpus a posteriori, we found that the NEJM and BMJ had none whereas the two anesthesiology journals had 17 (almost 13% of their total) and that 8 of them were full sentences.…”
Section: Phrasing Patterns In Ra and Review Titlessupporting
confidence: 82%
“…These reviews are usually invited submissions, and the opportunity to write them comes once a clinical researcher has gained the respect of peers. We anticipated finding few reviews [19] but nonetheless included this genre to make our work comparable to previous studies [14,15,17,19].…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations